Novel In Vitro Investigational Methods for Modeling Skin Permeation: Skin PAMPA, Raman Mapping - Stella Zsikó; Erzsébet Csányi; Anita Kovács; Mária Budai-Szűcs; Attila Gácsi; Szilvia Berkó (MDPI AG, 2020)
The human skin is marked as a standard by the regulatory agencies in the permeation study of dermal formulations. Artificial membranes can substitute human skin to some extent. Academicians and pharmaceutical corporations are focusing their efforts on developing standardized protocols and safe, reliable options to substitute human skin for carrying out permeability studies. Our research aim was to study the applicability of new techniques in the case of different types of dermal formulations. The skin parallel artificial membrane permeability assay (PAMPA) method and Raman mapping were compared to the gold-standard Franz cell method. A hydrogel and two types of creams were investigated as the most generally used dermal preparations. The values of the diffused drug were closer to each other in PAMPA and Franz cell measurement. The diffused amount of drug showed the same order for the different formulations. These results correlate well with the results of Raman mapping. Our conclusions suggest that all early screening examinations can be performed with model tools such as skin PAMPA supplemented with methods like Raman mapping as a semi-quantitative method.